Attosecond Transient Absorption Below the Excited States - Jinxing Xue; Xinliang Wang; Meng Wang; Cangtao Zhou; Shuangchen Ruan (Photonics, 2022)
In this study, the attosecond transient absorption (ATA) spectrum below the excited states of the helium atom was investigated by numerically solving the fully three-dimensional time-dependent Schrödinger equation. Under single-active electron approximation, the helium atom was illuminated by a combined field comprising of extreme ultraviolet (XUV) and delayed infrared (IR) fields. The response function demonstrates that the absorption near the central frequency (<semantics>ωX</semantics>) of the XUV field is periodically modulated during the overlapping between the XUV and IR pulses. Using the time-dependent perturbation, the absorption near <semantics>ωX</semantics> is attributed to the wavepacket excited by the XUV pulse. The wave function oscillating at the frequency of the XUV pulse was obtained. Furthermore, the chirp-dependent absorption spectrum near <semantics>ωX</semantics> potentially provides an all-optical method for characterizing the attosecond pulse duration. Finally, these results can extend to other systems, such as solids or liquids, indicating a potential for application in photonic devices, and they may be meaningful for quantum manipulation.